Hasil Validasi Soal Tes Hasil Belajar Mahasiswa Menggunakan Video Pembelajaran Kultur Jaringan Tanaman Berbasis Masalah - Melvariani Syari Batubara; Ayunda Sabrina Sormin (Magister Pendidikan Biologi, Universitas Negeri Medan, 2018)
The purpose of this study was to determine the results of the essay form validation test for student learning outcomes tests using problem-based plant tissue culture learning videos. The method used in this study is included in the development research to develop test questions on student learning outcomes by using problem-based plant tissue culture learning video products. The stages of the activities carried out are: (1) Research and Information colletion (research and data collection), (2) Planning (planning), (3) Develop Preliminary form of Product (development of the initial product draft), (4) Preliminary Field Testing ( initial field trials), (5) Main Product Revision (revised trial results), (6) Main Field Testing (main product field test), and (7) Operational Product Revision (product revision). From this study, the results show that where valid questions in cycle I are 10 questions, while in cycle II there are 11 valid questions. The first and second cycle test reliability is very high. Based on the calculation results of the above test differentiation in cycle I there are 7 excellent questions, 1 good question, 2 enough questions, while in cycle II there are 6 very good questions, 3 questions which are good, 1 problem is enough, and 1 problem is bad. Based on the index of difficulty in cycle I there are 10 questions that are easy, while in cycle II there are 10 questions that are easy and there is one problem in the medium category.